Drawings from a play-based intervention: Windows to the soul of rural Ugandan preschool children's artistic development. (February 2022) - Goodman, Geoff; Dent, Valeda F.; Tuman, Donna; Lee, SeungYeon
Abstract: Set in rural Uganda and using Lowenfeld (1947–1957) developmental stages model as a theoretical framework, this study describes an early childhood literacy project (Goodman and Dent, 2019 ) and the impact of the Storytelling/Story-Acting (STSA) play-based intervention on participating children's drawings. Ugandan children ages 3–5 were randomly assigned to participate in either the STSA play intervention ( n = 63) or a story-reading activity ( n = 60) for one hour twice weekly for six months. All children were assessed for school readiness skills before and after the six-month intervention. Two-hundred sixty-three drawings of four Ugandan children (two from the control group and two from the intervention group) who demonstrated the greatest change on a measure of school readiness were selected from the larger sample for analysis using the Formal Elements and Content rating scales. All four children demonstrated important deviations from Lowenfeld's developmental stages model, including a vertical baseline and faceless human figures observed in most of the drawings. Formal Elements but not Content changed over time. Girls performed differently from boys on both Formal Elements and Content. Artistic progression is relative to the cultural milieu in which the child is embedded. Highlights: The formal elements of Ugandan preschool children's drawings changed over six months. The content of Ugandan preschool children's drawings did not change over six months. Ugandan preschool children demonstrated the use of a vertical baseline and no faces. Researchers and therapists can use drawings to assess change in non-Western cultures.